Ready to Read : Space Cows - Seltzer, Eric; Disbury, Tom (New York Simon Spotlight, 2018)
Illustrations and simple, rhyming text reveal the day-to-day lives of cow space explorers, from what they look like, to how they keep busy, to how they deal with a noisy baby.
Pre-level one
Keywords: Cows -- Juvenile fiction; Astronauts -- Juvenile fiction; Stories in rhyme; Humorous stories; Cows -- Fiction; Astronauts -- Fiction; Stories in rhyme; Humorous Stories; JUVENILE FICTION / Readers / Beginner; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Animals / Cows; Early readers; Humorous fiction